Optical Antenna: A Key Enabling Arial For Device To Device Communication - Mohan, Anand (International Journal of Computer Sciences and Engineering, 2018)
The optical antenna transmits optical signals on nanometer scale. The nano-scale devices are expected to radiate in – THZ frequency range. The optical antenna has unique biological Application for communication networks to be analyzed. Its frequency response with high mode conductive antenna element for nano devices. The optical antenna has unique and key application for such types of area based configuration for optical communication devices. The optical antenna made-up nanoparticle like gold, particle because the calculation of three dimensions is possible in infrared band. In this research articles we have studied about antenna emission, distribution, characterization of terahertz (THZ) optical emission with high resonance of nanoantenna optical frequencies result. The wavelength optical antenna 400 nm nano-scale enable to study for far field radiation distribution.